INCREASING CUSTOMER LOYALTY THROUGH BRANDING AND PACKAGING STRATEGIES IN PADANG RESTAURANT BUSINESSES - Inneke Qamariah; Ibn Austrindanney Sina Azhar; Fauziah Kumalasari; Dio Agung Herubawa (RADJA PUBLIKA, 2024)
This community service program aims to improve branding and packaging of Padang restaurants in Medan. The main focus is to develop a strong brand identity and attractive packaging design to improve competitiveness and business sustainability. This program involves intensive training and mentoring for restaurant owners and staff, as well as periodic evaluation of the implementation of the strategies applied. This effort is expected to not only improve the aesthetics of the product but also strengthen emotional bonds with consumers, which in turn can increase customer loyalty. type the English abstract here. Fill abstract or abstract using Times New Roman 11. Abstract consists of subject matter, objectives, methods, results, and conclusions. Abstract is written in the form of one paragraph, without references, without abbreviations / acronyms, and without footones. Abstract is written not in the form of mathematics, questions and conjectures. The abstract is not the result of copying and pasting the sentences contained in the contents of the manuscript. The content of the abstract in English is a maximum of 150-300 words.